Proton conductivity of lanthanide nitrilotris-methylphosphonates - Salcedo, Inés R.; Bazaga-García, Montse; Pérez-Colodrero, Rosario Mercedes; Olivera-Pastor, Pascual; Losilla, Enrique R.; Cabeza-Díaz, Aurelio (My University, 2017)
Multifunctional metal phosphonates are acidic coordination polymers (CPs) with remarkable stability and proton conducting properties owing to their structure is usually composed of extended hydrogen-bond networks that favor proton transfer pathways [1]. In this communication, three different families of proton conductors based on lanthanide nitrilotris-methylphosphonates are examined. Compounds were isolated by crystallization at room temperature at pH <0.8 in the presence of. When chloride is presented in solution two families of compounds were isolated, depending on the concentration of chloride in solution: free-chloride 1D solids with formula Ln2(H3NMP)2(H2O)4]·4.5H2O [Ln= La3+] [2] or layered chloride-containing Ln(H4NMP)(H2O)2]Cl·2H2O [Ln= La3+ - Ho3+] materials [3]. In absence of chloride, a third series of compounds was obtained. This structural versatility leads to a wide range of proton conductivity varying between 3 × 10−4 S·cm−1 and 2 × 10−3 S·cm−1 as measured at 80 °C and 95% RH.
Keywords: Conductores orgánicos; coordination polymers; metal phosphonates; proton conductivity; solid-state chemistry; crystal structure